Develop Application of Photography Services MomenKita.com Web-based with Crowdsourcing Concept - Ismail Ismail; Sri Hariani Eko Wulandari; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Currently MomenKita is still in the development stage. MomenKita is an application or service that connects between tourists (clients) who need photographer services with photographers who are ready to capture the best moments of the client. The problem that occurs at this time is the client cannot take the photo by themselves maximally due to the absence of a professional photographer at an affordable price. And for the freelance or professional photographers, they cannot maximize their income due to marketing problem. Currently there are similar applications, but the client cannot choose a photographer who is in accordance with the client budget because the price has been determined by the application provider. The solution to solves these problems is the photography service ordering application that can assist clients in searching for information and ordering services for online photographer. By using the concept of crowdsourcing, giving photographers the freedom to manage the services they offer and clients can choose a photographer that fits their budget. As well as the development using the Scrum framework. The results showed that the application can help clients order photographer services by considering the budget, rating & review, and portfolio. Applications can also increase the photographer's chances to get more clients. Keywords: Photography, Photographer Services, MomenKita, Crowdsourcing, SCRUM